SAFE-GREEN (Safety and Efficiency for Green Economic Resilience): Integration of OSH in Sustainable Development in Asia–Africa - Yuliana Fadhilah Jayaningsih; Narisa Rayyana; Via Christy Eklesia Ginting (Economic and Business Horizon, 2026)
The development of a green economy in Asia and Africa is an urgent necessity amid the challenges of climate change, social inequality, and economic structural transformation. These efforts emphasize not only technological innovation, but also human-centered development as the main driver of sustainable growth. Although both regions have adopted the Sustainable Development Goals, global studies linking SDG 3 (Good Health and Well-being) and SDG 8 (Decent Work and Economic Growth) with occupational risk management are still limited. Furthermore, the integration of SDGs into occupational safety and health (OSH) systems and their impact on long-term economic resilience and growth have not been widely discussed. This study introduces the SAFE-GREEN (Safety and Efficiency for Green Economic Resilience) conceptual framework, which integrates occupational safety, resource efficiency, and sustainable development. The research method uses a qualitative approach through a review of international institutions’ literature and a comparative analysis of policies in ASEAN and the African Union. The results of the study show that effective Occupational Safety and Health  implementation can reduce economic losses, increase productivity, attract green industry investment, and strengthen long-term economic resilience, with workers as the main foundation of an inclusive green economy.